PENGARUH LIMBAH TERNAK SAPI PADA TANAMAN JAGUNG MANIS YANG DIPUPUK NITROGEN - Sudy, Fredrik Lero; Santoso, Mudji; Suminarti, Nur Edy (Jurnal Ilmu-Ilmu Pertanian, 2015)
The Nationally demand of Sweet corn demand has increased to 33.33%, but production is still low 4-8-ton ha-1, which is caused by low soil fertility. The efforts to improve soil fertility through nitrogen and animal waste fertilization is done. This experiment using the Split Spot Design Method with N as the main plot consisted dose of 150%, 100% and 50%. Subplot using the type of cow livestock waste, consisting of: without cow livestock waste, feces, urine and feces + urine. The results showed that the application of N, dose of 150% resulted in weight cob without husk per hectare (2.06 ton) diameter cob without husk (0.32 cm) higher and harvest index (3.8%) is smaller than the dose of N 50%. Applications livestock waste types feces + urine or urine, resulting in weight cob without husker hectare, diameter cob without husk, which was not significantly different from each 13.07 ton ha-1 and 13.13 ton ha-1, 5.12 cm and 5.02 cm both were significantly higher than feces or without livestock waste, while the harvest index showed that feces + urine is significantly higher than that of urine, feces and without livestock waste.